Development of a yeast-based CRISPR genome editing system for feline coronavirus - Zhang, Xiaohu; Zhu, Jingru; Zhang, Di; Zhang, Yueping (Frontiers in Microbiology, 2025)
IntroductionFeline infectious peritonitis (FIP), caused by feline coronavirus (FCoV), is a highly lethal disease characterized by systemic organ infection in cats. Current challenges of FIP include the absence of definitive diagnostic criteria, effective vaccines, and targeted therapies. Developing a robust genome editing toolkit is therefore critical to unraveling FCoV replication and pathogenesis mechanisms, elucidating viral protein functions, and identifying promising diagnostic and therapeutic targets.MethodsIn this study, we developed a yeast-based CRISPR genome editing system compatible with a TAR-generated FCoV infectious clone, enabling gene deletion, gene insertion, and point mutation with high efficiencies and accuracies.Results and discussionThis system not only will contribute to a better understanding of the pathogenic mechanisms of FCoV but also serves as a valuable platform for vaccine development. Furthermore, it offers a possible strategy for genome editing and reverse genetics for other coronaviruses.